Highly sulfur poisoning-tolerant BaCeO3-impregnated La0.6Sr0.4Co0.2Fe0.8O3−δ cathodes for solid oxide fuel cells. (21st September 2018) - Wang, Cheng Cheng; Luo, Dawei; Jiang, San Ping; Lin, Bin
Abstract: Electrochemical performance and sulfur (SO2 ) tolerance were studied on pristine La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) and BaCeO3 -impregnated LSCF (BaCeO3 –LSCF) composite cathodes of solid oxide fuel cells (SOFCs). Compared to pristine LSCF electrodes, BaCeO3 –LSCF composite electrodes exhibited reduced electrode polarization resistance and significantly lower activation energy for the O2 reduction reaction, indicating that BaCeO2 impregnation is effective at promoting the electrocatalytic activity of LSCF electrodes at low temperatures. Most significantly, BaCeO3 –LSCF cathodes show remarkable tolerance and resistance towards sulfur via the formation of BaSO4 instead of SrSO4 on the electrode surface, preventing excess Sr deficiency at the A-site of LSCF perovskite and thus mitigating the sulfur poisoning effect. BaCeO3 –LSCF cathodes show potential as highly active and excellent anti-sulfur oxygen electrodes for SOFCs.